Variation in insect assemblage and functional groups along a grazing gradient in an arid environment - Tadey, Mariana (2016)
Exotic livestock may affect plant and pollinator composition as well as their interactions. Changes in pollinatorassemblage (e.g. composition) may alter pollination process and, therefore, plant reproduction. This study examinedseven independent paddocks environmentally similar but with increasing livestock densities, in Patagonian MonteDesert. This allows investigating the response of different insect groups to livestock effect on vegetation along agrazing gradient. Water traps was used to capture insects (focusing on pollinators) and pollinator visitationfrequencies were measured in five of the most abundant native plant species of the region. Regressions betweenlivestock density and insect richness and abundance of the different functional groups of insects (dipterans,herbivores and pollinators) were performed. Insect assemblage was mostly composed, in decreasing order, byhymenopterans, coleopterans, dipterans and lepidopterans. Ordination analysis of insect composition showed a highcorrelation between the first axis and livestock density (r=0.95). In the first year of sampling, pollinators significantlydecreased in richness and wasps increased in abundance with livestock density. In the second year of sampling,pollinator abundance increased and herbivores decreased as livestock density increased. Unimodal ordinationanalyses showed that plant species were significantly associated to insect composition and livestock densitymarginally explained the variation in insect composition that visited the five studied plant species across paddocks.Interacting factors such as livestock density and climatic conditions may partially explain the patterns observed inthis work. Disturbances may alter the ecological scenarios, impoverishing the composition and abundance of floraand fauna. This study describes that changes in the density of exotic livestock can affect insect assemblageassociated to pollination process differently through the years. Changes through time may determine populationdynamic and their response to anthropogenic disturbances.